ScRALF3, a secreted RALF‐like peptide involved in cell–cell communication between the sporophyte and the female gametophyte in a solanaceous species. (25th February 2013) - Chevalier, Eric; Loubert‐Hudon, Audrey; Matton, Daniel P.
Summary Small peptides have been shown to regulate numerous aspects of plant development through cell–cell communication. These signaling events are particularly important during reproduction, regulating gamete development and embryogenesis. Rapid alkalinization factor (RALF)‐like genes, a large gene family that encodes secreted peptides, have specific or ubiquitous expression patterns. Previously, five RALF‐like genes with potential involvement during reproduction were isolated from Solanum chacoense. Here, we show that ScRALF3 is an important peptide regulator of female gametophyte development. Its expression, which is auxin‐inducible, is strictly regulated before and after fertilization. Down‐regulation of ScRALF3 expression by RNA interference leads to the production of smaller fruits that produce fewer seeds, due to improper development of the embryo sacs. Defects include loss of embryo sac nuclei polarization, as well as an increase in asynchronous division, accounting for cellular dysfunctions and premature embryo sac development arrest during megagametogenesis. ScRALF3 is expressed in the sporophytic tissue surrounding the embryo sac, the integument and the nucellus, as revealed by in situ hybridization and GUS staining. As expected for a secreted peptide, fluorescence from an ScRALF3–GFP fusion construct is detected throughout the secretory pathway. Therefore, the ScRALF3 secreted peptide may be directly involved in the regulation of multiple aspects of cell–cell communication between the female gametophyte and its surrounding sporophytic tissue during ovule development.